تأثير وسيلة بطاقة الصورة في تعليم المفردات في مدرسة انسان جنديكيا الثانوية باياكمبوه - Sari Uswatun Hasanah; Rizka Widayanti; M. Ramdhansyah; Moh. In’ami (MANAZHIM, 2023)
There is a problem in teaching vocabulary, namely many students do not master vocabulary well, so many people misunderstand. Errors include writing Arabic letters and correct vocabulary. This problem is caused by some teachers who do not apply teaching steps in accordance with existing theory. Meanwhile, it poses a problem. The purpose of this study was to determine the effect of the picture card method in understanding vocabulary, as well as in its translation at Islamic School Insan Cendekia Payakumbuh. In this study, researchers used quantitative methods, namely experimental research which was experimental research in schools with a quasy semi experimental design research with the pretest-posttest one group design type.Based on the results of the research as follows: First, the value group for the students' ability to know the understanding of vocabulary from the pre-test in the entire experimental semester is 1709 (∑X). The researcher found the largest value to be 75 and the smallest to be 38, with a mean of 58.93. Also, the researcher found the results of the students from the post-examination in the seventh semester. It is depicted that the whole number is 29 students (N)), and the result from the group value of the ability of students to know the understanding of vocabulary from the pre-test in the entire experimental class is 2172 (∑X). The researcher found the largest value 86 and the smallest value 56 with a mean of 74.89. Secondly, the researcher also found the students' results from the translation of vocabulary in pre-examination in the control class at Islamic School Insan Cendekia Payakumbuh. It is depicted that the whole number is 29 students (N), and the result of the group value of the ability of students to know the translation of vocabulary from the pre-exam in the control class as a whole is 1608 (∑X). The researcher found the largest value 73 and the smallest value 30 with a mean of 55.44.